Deconstructing The Meaning Of Pluralism: The Relevance Of Gus Dur's Fikrah Pluralism And Its Implications For Religious Life In Indonesia - Lainuvar (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
The purpose of this study is to describe Gus Dur's pluralism thinking and the resolution of conflicts between religions by Gus Dur. Therefore, it is essential to know how Gus Dur's pluralism thinking developed in Indonesia and its implications for the lives of religious people. The approach taken in this research is a qualitative approach with descriptive analysis, which is used because this research provides a clear and detailed explanation. The type of research is library research. Data collection comes from books and journal articles relevant to the theme. Data processing is done by analyzing the sources and sorting them, then choosing the source that is closest to the discussion in this study. The results of this study indicate that Gus Dur's pluralistic thought is slightly different. Gus Dur does not generalize all religions but recognizes that each religious adherent has its aspects of true belief. Gus Dur's thought of pluralism was realized with the revocation of the Presidential Instruction, the defense of the Ahmadiyah, and the rejection of establishing an Islamic state.